Forming national identity with televised cultural rituals: a critical discourse analysis of China’s Ancient Rhyme and New Voice—Qingming program - Li, Duruo; Sallam, Marwan H.; He, Zhiwu (Frontiers in Psychology, 2024)
Studies on media and national identity emphasize the need for a comprehensive and culturally sensitive approach to understanding the complex relationship between media and identity. This study used critical discourse analysis to examine the depiction of cultural rituals in the Ancient Rhyme and New Voice—Qingming program and its role in forming and reinforcing national identity in China. The program, broadcast on China Central Television, showcases three traditional Chinese cultural rituals: ancestor worship, agricultural rites, and spring outings. The analysis showed that the program aroused shared emotions, beliefs, and values among Chinese audiences, enhancing cohesion and cultural identification, and advancing the construction of Chinese national identity. The study highlights the importance of such cultural programs in promoting cultural identification and underscores the significant role of televised cultural rituals in shaping and reinforcing national identity in an increasingly globalized world.